Between Ecocentrism and Anthropocentrism: Situating Gandhian Philosophy of Environment - Tharakan, Koshy; George, Vidya Mary (Problemos, 2025)
While Gandhi is portrayed as an inspiration for proponents of ecocentrism, specifically Deep Ecologists like Arne Naess, Ramachandra Guha suggests that Gandhi was more concerned with anthropocentrism. Rather than ascertaining whether Gandhi was a Deep Ecologist, this paper aims to determine the implications of his philosophical anthropology for the Anthropocene. Dwelling on Gandhi’s comprehension of the other, including non-human nature, we situate Gandhian environmentalism between ecocentrism and anthropocentrism as a weak form of anthropocentrism that can be interpreted as ‘stewardship’ with the potential for an ethic of care. The Gandhian ideals of Swadeshi, Swaraj, and Sarvodaya are invoked to discuss the significance and alignment of Gandhi’s philosophy of environment to contemporary ideals of ecologically and socially sustainable societies.
Keywords: Deep Ecology; Gandhian Ethics; Advaita; Self and the Other; Environmentalism